Empirical evidence of nonlinearity in bottom up effect in a marine predator–prey system. (2nd November 2022) - Durant, Joël M.; Ono, Kotaro; Langangen, Øystein
Abstract : The strength of species interactions may have profound effects on population dynamics. Empirical estimates of interaction strength are often based on the assumption that the interaction strengths are constant. Barents Sea (BS) cod and capelin are two fish populations for which such an interaction has been acknowledged and used, under the assumption of constant interaction strength, when studying their population dynamics. However, species interactions can often be nonlinear in marine ecosystems and might profoundly change our understanding of food chains. Analysing long-term time series data comprising a survey over 37 years in the Arcto-boreal BS, using a state-space modelling framework, we demonstrate that the effect of capelin on cod is not linear but shifts depending on capelin abundance: while capelin is beneficial for cod populations at high abundance; below the threshold, it becomes less important for cod. Our analysis therefore shows the importance of investigating nonlinearity in species interactions and may contribute to an improved understanding on species assemblages.